Influência do uso de arames inoxidáveis ferríticos nas características da zona fundida de um aço inoxidável ferrítico com 17% de cromo biestabilizado - Rodrigo Pereira Madeira (2007)
Stainless Steels have been extensively used in automotive exhaust systems. Recently, the use of ferritic stainless steel welding wires have been increasing for joining parts during the fabrication of those systems because it can reduce the product cost and optimize its performance under thermal mechanic fatigue. This work compares the metallurgical and mechanical characteristics of the fusion zones obtained by the use of welding wires 430Ti and 430LNb. The influence of shielding gases Ar2%O2 and Ar2%N3%CO2 was also studied. In order to check the mechanical properties, a detailed study of welding joint behavior during Erichsen test was done. Tension and bending test were also used. The microstructure was analyzed using optical and electronic microscopes, revealing the main characteristics of melting zones obtained by the use of these welding wires and shielding gases. The influence of stabilizingelements Ti and Nb and the effect of shielding gases in the melting zone characteristics were discussed. It could be concluded that the Erichsen test was effective to evaluate the welded bead ductility presenting higher sensibility than the conventional tests. The welding wire 430LNbshowed a ductility behavior as good as 308LSi, independent of the shielding gas. On the other hand, the 430Ti presented good ductility when used together with the shielding gas Ar2%O2, but, the use of 430Ti and Ar2%N3%CO2 at the same time determined a ductility loss in themelted zone because of precipitation in grain boundary.